Climatic and insolation control on the high-resolution total air content in the NGRIP ice core - O. Eicher; M. Baumgartner; A. Schilt; J. Schmitt; J. Schwander; T. F. Stocker; H. Fischer (Climate of the Past, 2016)
Because the total air content (TAC) of polar ice is directly affected by the atmospheric pressure and temperature, its record in polar ice cores was initially considered as a proxy for past ice sheet elevation changes. However, the Antarctic ice core TAC record is known to also contain an insolation signature, although the underlying physical mechanisms are still a matter of debate. Here we present a high-resolution TAC record over the whole North Greenland Ice Core Project ice core, covering the last 120 000 years, which independently supports an insolation signature in Greenland. Wavelet analysis reveals a clear precession and obliquity signal similar to previous findings on Antarctic TAC, with a different insolation history. In our high-resolution record we also find a decrease of 4–6 % (4–5 mL kg −1 ) in TAC as a response to Dansgaard–Oeschger events (DO events). TAC starts to decrease in parallel to increasing Greenland surface temperature and slightly before CH 4 reacts to the warming but also shows a two-step decline that lasts for several centuries into the warm interstadial. The TAC response is larger than expected considering only changes in air density by local temperature and atmospheric pressure as a driver, pointing to a transient firnification response caused by the accumulation-induced increase in the load on the firn at bubble close-off, while temperature changes deeper in the firn are still small.